Study of fracture parameters and complete fracture process of concrete at low temperatures using an energy approach. (15th March 2022) - Fan, Bing; Guo, Bowen; Gao, Yuqin; Yu, Jiang; Hu, Shaowei
Highlights: The fracture properties of concrete at low temperatures were studied using an energy approach. The equivalence between stress intensity factors and energy parameters was verified. Initial fracture energy release rate was employed to determine crack propagation in concrete. The effect of temperature on the fracture parameters and crack extension resistance curve were presented. Abstract: The fracture parameters and complete fracture process of concrete under low-temperature environment were studied by using an energy approach. The fracture parameters including the initial fracture energy release rate G I c ini, unstable fracture energy release rate G I c un and critical cohesive energy release rate G I c c were determined, and the accuracy of the double-G fracture model was verified by the unstable fracture energy release rate G Ic un ∗ . Furthermore, the equivalence of the double-G fracture model and double-K fracture model was verified by the effective double-K fracture toughness ( K I c ini ¯ and K I c un ¯ ). Finally, the complete fracture process of concrete was simulated by taking G I c ini as the condition of each crack propagation. The availability of the numerical method was proved, and the effect of temperature on the crack extension resistance curve was investigated.